Effect of autologous platelet-rich plasma on optical quality and visual outcomes following implantation of a trifocal diffractive intraocular lens - Kun-Hoo Na; Bo Young Lee; Hye Jin Cho; Joon Young Hyon (PLoS ONE, 2026)
Purpose To evaluate the effect of autologous platelet-rich plasma (PRP) eye drops on optical quality and visual acuity in eyes implanted with a trifocal diffractive intraocular lens (IOL). Methods In this retrospective cohort study of 128 eyes from 128 patients undergoing femtosecond laser-assisted cataract surgery with implantation of the CNWT Clareon PanOptix (Alcon Inc.) IOL, patients were assigned to one of two groups: the PRP group (n = 62), which received postoperative PRP eye drops, and the conventional treatment group (n = 66). At 3 weeks postoperatively, optical parameters—including the objective scatter index (OSI), modulation transfer function (MTF) cutoff, and Strehl ratio (SR)—were measured with a double-pass system. Uncorrected distance visual acuity (UDVA) and corrected distance visual acuity (CDVA) at 4 m, as well as uncorrected near visual acuity (UNVA) at 40 cm, were recorded in logMAR units. Results The PRP group demonstrated superior optical quality across all measured parameters compared to the control group, with lower OSI (1.60 vs. 3.14), higher MTF cutoff (31.93 vs. 19.90 cycles/degree), and higher SR (0.15 vs. 0.12) (all P < 0.001). Visual acuity was also significantly better in the PRP group, with lower mean logMAR UDVA (0.05 vs. 0.10; P < 0.001), CDVA (0.01 vs. 0.05; P < 0.001), and UNVA (0.13 vs. 0.18; P = 0.007). Multivariate analyses confirmed that the use of PRP eye drops was independently associated with improvements in all three optical parameters: OSI (B = −1.488), MTF cutoff (B = 12.038), and SR (B = 0.039) (all P < 0.001). Conclusions The use of autologous PRP eye drops improves optical quality and visual acuity at all distances following trifocal diffractive IOL implantation. PRP eye drops may serve as a beneficial adjunct for postoperative management in patients undergoing this procedure.